Energy Harvesting from the Stray Electromagnetic Field around the Electrical Power Cable for Smart Grid Applications - Farid Ullah Khan (The Scientific World Journal)
For wireless sensor node (WSN) applications, this paper presents the harvesting of energy from the stray electromagnetic field around an electrical power line. Inductive and capacitive types of electrodynamic energy harvesters are developed and reported. For the produced energy harvesters, solid core and split-core designs are adopted. The inductive energy harvester comprises a copper wound coil which is produced on a mild steel core. However, the capacitive prototypes comprise parallel, annular discs separated by Teflon spacers. Moreover, for the inductive energy harvesters’ wound coil and core, the parametric analysis is also performed. A Teflon housing is incorporated to protect the energy harvester prototypes from the harsh environmental conditions. Among the inductive energy harvesters, prototype-5 has performed better than the other harvesters and produces a maximum rms voltage of 908 mV at the current level of 155 A in the power line. However, at the same current flow, the capacitive energy harvesters produce a maximum rms voltage of 180 mV. The alternating output of the prototype-5 is rectified, and a super capacitor (1 F, 5.5 V) and rechargeable battery (Nickel-Cadmium, 3.8 V) are charged with it. Moreover, with the utilization of a prototype-5, a self-powered wireless temperature sensing and monitoring system for an electrical transformer is also developed and successfully implemented.